Determination of the high temperature elastic properties and diffraction elastic constants of Ni-base superalloys. (5th January 2016) - Aba-Perea, P.E.; Pirling, T.; Withers, P.J.; Kelleher, J.; Kabra, S.; Preuss, M.
Abstract: The diffraction elastic constants and phase specific elastic constants of two Ni-base Superalloys, Inconel 718 (as-quenched and aged) and Udimet 720LI (aged) have been determined as a function of temperature by means of in-situ loading using time-of-flight neutron diffraction. Experiments were carried out between room temperature and 750 °C in order to support future in-situ residual stress analyses during ageing treatments. In the case of Udimet 720LI, Rietveld analysis of the diffraction data revealed very similar elastic constants for γ and γ′ suggesting a simplified single-phase model can be used for the analysis of the diffraction data. As one would expect, the Young's moduli fall with increasing temperature for Inconel 718 from 220 GPa at room temperature to 140 GPa at 700 °C with a knee in the curve at around 500 °C. The Udimet 720 is around 15–20 GPa stiffer over the temperature range studied and the individual peaks fall in a similar manner. In addition in all cases the diffraction elastic constants (DECs) of the (311), (220), (200) and (111) reflections varied linearly according to the crystallographic anisotropy factor as expected for all temperatures with the degree of anisotropy increasing with increasing temperature. Graphical abstract: Highlights: The variation in diffraction elastic constants of Ni-base superalloys with temperature were determined. Elastic constants of the γ and γ′ phases in Udimet 720LI are similar. The diffraction elastic constants decrease with increasing temperature. The elastic constants of Udimet 720LI remain higher than those of Inconel 718.